Nephrology key information for internists - Sohail Abdul Salim; Juan A. Medaura; Bharat Malhotra; Vishnu Garla; Shradha Ahuja; Nicki Lawson; Amaleswari Pamarthy; Hardik Sonani; Karthik Kovvuru; Venkataraman Palabindala (Greater Baltimore Medical Center, 2017)
Hospitalists and primary care physicians encounter renal disease daily. Although most cases of acute kidney injury (AKI) are secondary to dehydration and resolve by giving fluids, many cases of AKI are due to not uncommon but unfamiliar causes needing nephrology evaluation. Common indications to consult a nephrologist on an emergency basis include hyperkalemia or volume overload in end stage renal disease patients (ESRD). Other causes of immediate consultation are cresenteric glomerulonephritis / rapidly progressive glomerulonephritis in which renal prognosis of the patient depends on timely intervention. The following evidence-based key information could improve patient care and outcomes. Abbreviations: AKI: Acute kidney injury ESRD: End stage renal disease patients